Optimization of Ultrasound-Assisted Extraction of Antioxidant Polyphenols from the Seed Coats of Red Sword Bean (Canavalia gladiate (Jacq.) DC.) - Yue Zhou; Xiao-Yu Xu; Ren-You Gan; Jie Zheng; Ya Li; Jiao-Jiao Zhang; Dong-Ping Xu; Hua-Bin Li (MDPI AG, 2019)
The seed coat of red sword bean (Canavalia gladiata (Jacq.) DC.) is rich in antioxidant polyphenols. It is often discarded as a byproduct with the consumption of red sword bean, since it is very thick and not consumed by people. The aim of this study was to develop an ultrasound-assisted extraction method to extract natural antioxidants from the seed coats. The extraction process was optimized by using response surface methodology. After the single-factor experiments, three key factors, including ethanol concentration, liquid/solid ratio, and extraction time, were selected and their interactions were studied using a central composite design. The optimal extraction condition was 60.2% hydroethanol, a liquid/solid ratio of 29.3 mL/g, an extraction time of 18.4 min, an extraction temperature of 50 °C, and ultrasound power of 400 W. Under the optimal conditions, antioxidant activity of the extract was 755.98 ± 10.23 μmol Trolox/g dry weight (DW), much higher than that from maceration (558.77 ± 14.42 μmol Trolox/g DW) or Soxhlet extraction (479.81 ± 12.75 μmol Trolox/g DW). In addition, the main antioxidant compounds in the extract were identified and quantified by high-performance liquid chromatography−diode array detection−tandem mass spectrometry (HPLC−DAD−MS/MS). The concentrations of digalloyl hexoside, methyl gallate, gallic acid, trigalloyl hexoside, and digallic acid were 15.30 ± 0.98, 8.85 ± 0.51, 8.76 ± 0.36, 4.27 ± 0.21, and 2.89 ± 0.13 mg/g DW. This study provides an efficient and green extraction method for the extraction of natural antioxidants from the bean coat of red sword bean. The extract of antioxidants might be added into functional foods or nutraceuticals with potential beneficial functions.